The Mode is not the Methods: Assessing Changes in Biking, Walking and Transit in California using the 2012 CHTS and 2017 NHTS - Susie Pike; Susan Handy (Findings)
Data from the 2012 California Household Travel Survey (CHTS) and the 2017 National Household Travel Survey (NHTS) suggest that biking, walking, and transit use in California decreased over this five-year period. In light of the California Department of Transportation (Caltrans) and State Transportation Agency (CalSTA)'s goal of tripling walking and doubling biking and transit use in their most recent strategic plan, these unanticipated results raised concerns about whether these decreases stem from methodological differences and choices about analysis between the two surveys. In this study, we evaluate numerous differences between the two surveys to assess whether the changes are likely to be real, or the result of methodological differences between the CHTS and the NHTS. We find that overall, the use of biking, walking and transit decreased over this time period, and these results are generally consistent across methodological differences and analysis choices.